Investigation of Optical Ionization of Strontium via 5s21S0 ⟶ 5s5p 3P1° ⟶ 5s5d 3D2 ⟶ 4dnp (or 4ndf, n = 39) for Isotope Selectivity Enhancement - Donguk Cheon; Yoshihiro Iwata; Masabumi Miyabe; Ikuo Wakaida; Shuichi Hasegawa (Journal of Spectroscopy)
We investigated a promising three-step resonance ionization scheme of strontium (Sr) 5s21S0 ⟶ 5s5p 3P1° ⟶ 5s5d 3D2 ⟶ 4dnp (or 4dnf, n = 39) using the first-step intercombination transition for the enhancement of isotope selectivity. The power broadening observed in the 2nd transition indicates that laser power of less than 0.2 mW is sufficient for saturating this transition. Isotope separation can be successfully expected with application of the 3rd transition due to the narrow width of the 4dnp (or 4dnf, n = 39) autoionization level, paving the way for analysis of trace 90Sr in environmental applications.